Prevalence of peripheral neuropathy in children with transfusion-dependent thalassemia: A hospital-based cross-sectional study - Aniruddha Rathore; Mukesh Dhankar; Sharmila B. Mukherjee; Suvasini Sharma; Shailaja Shukla; Piali Mandal (Journal of Family Medicine and Primary Care)
Background: Our study aimed to determine the prevalence of Peripheral Neuropathy (using nerve conduction studies (NCS)) in children with transfusion-dependent thalassemia aged between 5 to 18 years and to study its correlation with chronic anemia, ferritin levels, chelation status, annual transfusion requirement, deficiency of serum Vitamin B12, and Folate levels. Methods: In this hospital-based cross-sectional study, 100 eligible children were enrolled in a tertiary care teaching hospital in New Delhi, India. Neurological examinations focusing on peripheral neuropathy followed by NCS were performed on all the patients. Age-wise cutoff values outside of 2.5 SD of normal were taken as abnormal. Results: None of the children had clinical features of peripheral neuropathy, although 77% had abnormalities in NCS. Of these, 33% had pure motor nerve changes, 7% had pure sensory nerve changes, 1% had abnormal F responses, and 26% had mixed nerve changes. These changes correlated significantly with chronic anemia and duration of iron chelation but not with other factors. Conclusion: In children with transfusion-dependent thalassemia who do not exhibit any neurological signs or symptoms, however, it is not uncommon to observe abnormal NCS at an average hemoglobin (Hb) level of less than 9.5 g/dl. Further comprehensive case-control studies are necessary to determine if a more specific Hb target range of 9.5 to 10.5 g/dl is appropriate and to investigate the potential impact of chelation therapy on these changes.